Comparison of Performance with Wide Dynamic Range Compression and Linear Amplification - Kam, Anna C. S.; Wong, Lena L. N. (Journal of the American Academy of Audiology, 1999)
This study compared subject performance and preference using a compression-limiting hearing aid set to linear amplification (program 1) and wide dynamic range compression (WDRC, program 2). The frequency responses of the hearing aid were matched to a 65 dB SPL signal and maximum output to a 90 dB SPL signal. Twenty subjects with moderate to moderately severe sensorineural hearing loss were tested. Speech recognition scores and speech reception thresholds were obtained both in quiet and in noise. Subjective preference for WDRC or linear amplification was measured via a paired-comparison procedure on "loudness appropriateness,” “clarity," and "pleasantness" to continuous discourse presented in quiet and in noise. Results suggested that WDRC yielded better speech intelligibility in quiet for low-level signals and no difference in speech intelligibility in noise compared to linear amplification. Subjects preferred WDRC for loudness to both high- and low-level signals and for pleasantness to high-level signals.Abbreviations: ANOVA = analysis of variance, AVC = automatic volume control, CL = compression limiting, CVR = consontant-vowel-ratio, HINT = Hearing In Noise Test, Ρ = program, REIG = real-ear insertion gain, REIR = real-ear insertion response, SNR = signal-to-noise ratio, SRS = speech recognition score, SRT = speech reception threshold, WDRC = wide dynamic range compression
Keywords: Linear amplification; speech intelligibility; subjective preference; wide dynamic range compression